Q-switched Yb-doped fiber laser operating at 1073 nm using a carbon nanotubes saturable absorber - Al-Masoodi, A.H.H.; Ismail, M.F.; Ahmad, F.; Kasim, N.; Munajat, Y.; Ahmad, Harith; Harun, Sulaiman Wadi (John Wiley & Sons, 2014)
A stable passive Q-switched Ytterbium-doped fiber laser (YDFL) operating at 1073-nm region is demonstrated using single-walled carbon-nanotubes (SWCNTs) as a saturable absorber (SA). The SA is prepared using polyvinyl alcohol (PVA) as a host polymer and integrated in the YDFL ring cavity by sandwiching the SWCNT/PVA thin film between two fiber connectors. A stable pulse train is achieved with 17.1-kHz repetition rate, 6.45-μs pulse width, and 3.1-nJ pulse energy at the threshold 980-nm pump power of 95.4 mW. As the pump power increases to 117.5 mW, the pulse train repetition rate also rises to 23.6 kHz. The shortest pulse width of 3.11 μs and pulse energy of 4.4 nJ are achieved at the maximum pump power of 117.5 mW